Pengaruh Harga, Brand Image, Dan Iklan Televisi Terhadap Minat Membeli - Onnasis, Jeany Priscila; Suryadi , Nanang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to determine the influence of price, brand image, and television advertising on the intention to purchase online tutoring packages from Ruangguru among high school students in Malang City. This type of research is explanatory research that explains the causal relationship between variables through hypothesis testing. The study used a sample of 140 respondents. The sampling method employed was non-probability sampling with purposive sampling technique. The data analysis included descriptive analysis, classical assumption tests, multiple linear regression analysis, and hypothesis testing. Based on the testing of the three variables, it can be concluded that the price, brand image, and television advertising have a positive and significant impact on the intention to purchase online tutoring packages from Ruangguru among high school students in Malang City. The results of this research indicate that the price offered by Ruangguru corresponds to the benefits received when purchasing the product. Ruangguru is perceived as a trusted tutoring service. The message conveyed by Ruangguru's television advertising is effectively communicated to the audience. This means that the intention to purchase online tutoring packages from Ruangguru among high school students in Malang City is influenced by price, brand image, and television advertising. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh harga, brand image, iklan televisi terhadap minat membeli paket bimbingan belajar online Ruangguru pada siswa SMA di Kota Malang. Jenis penelitian ini adalah explanatory research yang menjelaskan hubungan kausal antara variabel-variabel melalui pengujian hipotesis. Penelitian ini menggunakan sampel sebanyak 140 responden. Pengambilan sampel menggunakan metode non-probability sampling dengan teknik purposive sampling. Analisis data yang dilakukan adalah analisis deskriptif, uji asumsi klasik, analisis regresi linier berganda dan uji hipotesis. Dari hasil pengujian terhadap ketiga variabel dapat disimpulkan bahwa variabel harga, brand image, dan iklan televisi berpengaruh positif dan signifikan terhadap minat membeli paket bimbingan belajar online Ruangguru pada siswa SMA di Kota Malang. Hasil dari penelitian ini menunjukkan harga yang diberikan Ruangguru sesuai dengan manfaat yang diterima ketika membeli produk. Ruangguru dicitrakan sebagai bimbel yang terpercaya. Isi pesan yang disampaikan oleh iklan televisi Ruangguru dapat disampaikan dengan baik kepada penonton. Hal ini berarti bahwa minat membeli paket bimbingan belajar online Ruangguru pada siswa SMA di Kota Malang dipengaruhi oleh harga, citra merek, dan iklan televisi.